Comparative toxicity of imidacloprid, of its commercial liquid formulation and of diazinon to a non-target arthropod, the microcrustacean Daphnia magna - Jemec, Anita; Tišler, Tatjana; Drobne, Damjana; Sepčić, Kristina; Fournier, Didier; Trebše, Polonca (Chemosphere (Oxford), 2007)
Imidacloprid (IMI) is at the moment the insecticide with the world’s fastest growing sales and is considered possible replacement for the widely used organophosphorus pesticide, diazinon, which is subject to phased revocation in many countries. In this study, biochemical, reproductive and survival parameters of the water flea ( Daphnia magna) after chronic exposure to IMI, its commercial liquid formulation Confidor SL 200 and diazinon are presented and compared. According to the lowest observed effect concentrations, diazinon is more toxic to the reproduction of D. magna than IMI and Confidor SL 200, which exert similar toxicity. The same was observed for the survival, except that Confidor SL 200 is more toxic than IMI. In polluted aquatic environments, the actual levels of diazinon are potentially chronically hazardous to the reproduction of D. magna (risk quotient > 1). According to very few measured environmental levels of IMI, the latter is not expected to be chronically hazardous, unless it is accidentally spilled in a small pond. In such case, the predicted concentrations of IMI would present a potential chronic risk to D. magna, and a potential acute risk to other aquatic invertebrates. In the future, higher environmental levels of IMI are expected due to its increasing use and physico-chemical properties. The literature survey summarized in this work suggests that further ecotoxicological studies with a broader spectrum of aquatic organisms are needed before IMI is classified as safer than currently applied pesticides.